Moral blame and rational criticism. (European Journal of Philosophy, 2022)
A central issue in practical philosophy concerns the relation between moral blameworthiness and normative reasons. As there has been little of direct exchange between the debate on reasons and the debate on blameworthiness, this topic has not received the attention it deserves. In this paper, I consider two notions about blameworthiness and reasons that are fundamental in respective field. The two notions might seem incontrovertible when considered individually, but I argue that they together entail claims that are highly contentious. In particular, I maintain that they entail unreasonable and contradictory claims since the practices of moral blame and rational criticism diverge with regard to three dimensions: justification, response, and function. Thus, we need to give up one of the principal notions. The solutions to this puzzle suggest that the connection between reasons and rationality is weaker than standardly presumed in metaethics.